Predicting Environmental Behavior at Polluted Rivers in Terengganu using Structural Equation Modeling - Wan Nor Azilawanie Tun Ismail and Aziz Amin (International Journal of Advanced Science and Technology, 2020)
Mismanagement of environmental sustainability issues especially on river qualityshows an increase every year. As the environmental effects toward today’s and futuregeneration that will have to depend on the protection of the ecosystem come in manyways, the need to create a more environmentally responsible society has risen. It is a dutyto conserve water sources concerning its quality and quantity before they are completelywiped out. This study aims to identify the determinants of the behavior of people living inpolluted rivers in Terengganu. This study was conducted in a quantitative approach usinga survey method for data collection. A total of 373 respondents were selected by clustersampling. The study site was conducted at ten rivers that were considered polluted inTerengganu. Instruments used to collect the data were questionnaire form and analyzedwith software namely IBM Statistical Package for Social Science (SPSS) and Analysis ofMoment Structure (AMOS). The findings show that knowledge and exposure toenvironmental messages through the media is a dominant factor influencing respondents'behavior on river conservation. As a result, this study can form a united and positive civilsociety. It is vital to create a progressive society that cares about the environment andunderstands the needs of current and future generations